Effect of the water sorption on the mechanical response of microcrystalline cellulose‐based composites for art protection and restoration. Issue 18 (10th April 2014) - Cataldi, Annalisa; Dorigato, Andrea; Deflorian, Flavio; Pegoretti, Alessandro
ABSTRACT: Thermoplastic composites based on a commercial acrylic matrix widely used in the field of art protection and restoration (Paraloid B72) and various concentrations (up to 30 wt %) of microcrystalline cellulose powder (MCC) were prepared by melt‐compounding and compression molding. The mechanical behavior of the resulting materials conditioned at a temperature of 23°C and a relative humidity level of 55% was compared to that of the corresponding dried materials. Even though the moisture absorption of the filler was lower than the neat matrix, the maximum moisture content increased with the MCC amount, probably due to the preferential water diffusion path through the microvoids and/or the filler‐matrix interface. Although the increase of moisture content for filled samples, DMTA analysis evidenced a stabilization upon MCC introduction, with an increase of the storage modulus and a decrease of the thermal expansion coefficient proportional to the filler loading. A similar trend was displayed by the corresponding dried materials. The tensile elastic modulus and the ultimate properties such as the stress at break and the tensile energy to break (TEB) of conditioned samples increased proportionally to the filler amount. On the contrary, the failure properties of dried composites were negatively affected by the presence of the microcellulose. It is worthwhile to report that a significant improvement of the creep stability was induced by MCC introduction both for dried and conditioned samples. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2014, 131, 40741. Abstract :